Religious Dimensions in Transhumanist and Posthumanist Philosophies of Science - Juozelis, Evaldas (Conatus - Journal of Philosophy, 2021)
The article discusses transhumanism and posthumanism as marginal trajectories of the modern philosophy of science, which, however, distinctly influence the mainstream narrative of science and societal relations. Among the decisive determinants of this impact is trans/posthumanism’s para-religious content that replenishes a conceptualised process of cutting-edge scientific practices and ideals. In particular, transhumanism and posthumanism evolve as ideological exploiters of seemingly obsolete forms of religiosity, for they simultaneously exploit and reinvent the entire apparatus of the scientific, political, and moral activity in Western societies. Avant-garde secular worldviews tend to be religious in the sense that their ultimate quest is the transformation of humans into certain historical entities, which are capable of rearranging their own systems of order.